Association of SHI coverage and level of healthcare utilization and costs in the Philippines: a 10-year pooled analysis - Haw, Nel Jason L (Archīum Ateneo, 2019)
Background The Philippine Health Insurance Corporation (PhilHealth), which manages the Philippine national health insurance program, is a critical actor in the country’s strategy for universal health coverage. Over the past decade, PhilHealth has passed significant coverage, benefits and payment reforms to contain costs and improve the affordability care for high-cost diseases, inpatient care and select outpatient services. Methods We studied the association of PhilHealth with health care utilization and health care costs using three rounds of the Philippine Demographic and Health Survey with data on individual outpatient and inpatient visits from 2008 to 2017. Results PhilHealth membership was associated with 42% greater odds of outpatient utilization and 47–100% greater odds inpatient utilization depending on survey year. Depending on facility type, use of PhilHealth to pay for care was associated with higher average health care costs of 244–865% for outpatient care and 135–206% for inpatient care. Conclusions PhilHealth has likely decreased barriers to health care utilization but may have inadvertently driven up health care costs in the country. Results align with past studies that suggest that reforms in the prior decade have done little to contain health care costs for Filipinos.